Rules, practices and identities: an interactional sociolinguistic study of Queen’s Speech Debates in the House of Lords - Howard, Victoria (2020)
This PhD thesis adopts an interactional sociolinguistic approach to analysing how speakers in Queen’s Speech Debates in the House of Lords construct intersecting identities as they negotiate institutional and interactional rules and practices. It argues that speakers commonly draw upon stereotypes and dominant discourses of gender, age, social class and national identity in the construction of legitimate ‘peer’ identities. In order to demonstrate oratory skills valued in this community of practice (CofP, Eckert and McConnell-Ginet, 1992a), speakers (particularly but not exclusively men) tend to orientate towards hegemonic masculinities, a formal, elite register and advanced life stages, effectively reinforcing the notion of a ‘prototypical peer’. The linguistic repertoire is characterised by resources such as rivalrous humour, militarised language and sexism, which invoke ‘fraternal networks’ (Walsh, 2001) and may not be equally available to all peers. Newer, younger, less politically-experienced, and particularly women peers, appeared more likely to observe procedural rules and politeness norms than long-serving men. As well as echoing findings from studies of the House of Commons (e.g., Childs, 2004a, Shaw, 2006) which have suggested that as ‘interlopers’ (Eckert, 1998) women may be reluctant to break rules, these findings emphasise the value of an intersectional approach. Finally, this thesis has found that outlying identities are not universally disadvantageous. First, several non-English peers used national identity constructions in order to justify breaching rules and practices; and second, women made considerable use of subversive humour to explicitly engage with idiosyncratic rules and practices. These findings highlight the complexity of competing discourses and power relations, which do not necessarily consistently render certain groups powerful or powerless (Baxter, 2015).